Parenteral Zinc Intake in Newborns With Jejunostomy or Ileostomy: Results of a Monocentric Cohort Study. Issue 4 (April 2020) - D'Aniello, Roberta; Terquem, Elise L.; Poupon, Joël; Assaf, Ziad; Kermorvant-Duchemin, Elsa; Maggio, Luca; Lapillonne, Alexandre
ABSTRACT: Objectives: The aim of the study was to assess zinc status of newborns with parenteral nutrition with or without a small bowel stoma, to determine the incidence of zinc deficit, and to determine the clinical factors associated with plasma zinc levels. Methods: Monocentric cohort study including all liveborn infants receiving zinc parenteral intake at 500 μg · kg −1 · day −1 and who benefited from at least 1 plasma zinc assessment during hospitalization. Results: Sixty-eight dosages of zinc were performed in 50 newborns, divided into 3 groups (no stoma = 26, jejunostomy = 11, ileostomy = 13). Thirty-seven of the 50 infants were born preterm. The mean ± standard deviation plasma zinc was 14.9 ± 4.3 μmol/L and was similar among the 3 groups. Sixty-four percent, 3%, and 34% of zinc values were within, below, and above the normal range, respectively. In infants with jejunostomy, only 1 plasma zinc value (5%) was below the reference range. Plasma zinc levels were negatively correlated with stoma output ( r 2 = −0.449; P = 0.013). In contrast to patients with limited intestinal losses (ie, no stoma and ileostomy groups) no association between zinc levels and postmenstrual age was observed in infants with a jejunostomy suggesting that 500 μg · kg −1 · day −1 was adequate not only in preterm infants but also in term infants with a jejunostomy. Conclusion: Plasma zinc levels decrease significantly with the increase of stoma output volume of newborns with small bowel stoma. Zinc deficit was prevented in newborns with a small bowel stoma receiving of 500 μg · kg −1 · day −1 of parenteral zinc. Abstract : Supplemental Digital Content is available in the text